2022
DOI: 10.3390/en15072608
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of LMNO Cathodes Produced with Pullulan or PEDOT:PSS Water-Processable Binders

Abstract: The aim of this paper is to demonstrate lithium metal battery cells assembled with high potential cathodes produced by sustainable processes. Specifically, LiNi0.5Mn1.5O4 (LMNO) electrodes were fabricated using two different water-processable binders: pullulan (PU) or the bifunctional electronically conductive poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT:PSS). The cell performance was evaluated by voltammetric and galvanostatic charge/discharge cycles at different C-rates with 1M LiPF6 in 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In our previous studies, 27 , 28 we demonstrated that the lithiation/delithitation processes are highly reversible for both NMC532 and LNMO-bulk electrodes. These electrodes can be charged/discharged over hundreds of cycles without significant structural, morphological, or compositional changes, when operated in LP30 electrolyte.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…In our previous studies, 27 , 28 we demonstrated that the lithiation/delithitation processes are highly reversible for both NMC532 and LNMO-bulk electrodes. These electrodes can be charged/discharged over hundreds of cycles without significant structural, morphological, or compositional changes, when operated in LP30 electrolyte.…”
Section: Resultsmentioning
confidence: 76%
“…These reversible peaks can be assigned to the Mn 4+ /Mn 3+ , Ni 3+ /Ni 2+ , and Ni 4+ /Ni 3+ redox couples, respectively. 28
Figure 1 Cyclic voltammograms of bulk (A) NMC532- and (B) LNMO-based electrodes in the electrolyte LP30, in a Swagelok-like cell including a metallic lithium disk serving both counter and reference electrode. Potential scan rate 50 μV s -1 .
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically with PEDOT:PSS a greater utilization of the active material was achieved compared to a similar PVdF‐based electrode (Figure 2). [35] …”
Section: Outcomes Of the Projectmentioning
confidence: 99%